Whole-Exome Sequencing Identified Genes Responsible for Thoracic Aortic Aneurysms and Dissections in three Chinese Families - Guo, Renle; Du, Pengcheng; Pei, Yifei; Yang, Jin; Li, Shuangshuang; Chang, Sheng; Sun, Huiying; He, Xiaomin; Dong, Jian; Zhou, Jian; Jing, Zaiping (Frontiers in Genetics, 2022)
Thoracic aortic aneurysms and dissections are precarious conditions that often cannot be diagnosed with fatal outcomes. Over the last few years, pathogenic variants in numerous genes have been identified that predispose to heritable presentations of TAAD. An evidence-based strategy for the selection of genes to test in familial TAAD helps inform family screening and intervention to prevent life-threatening events. Using whole-exome sequencing, four members of three unrelated families clinically diagnosed with TAAD were used to identify the genetic origin of the disorder. Variant evaluation was carried out to detect the pathogenic mutation. Our studies suggest that mutations of COL3A1 and ACTA2 are responsible for familial TAAD. In addition, we highlight FBLN5, FBN1, SLC2A10, FBN2, and NOTCH1 as candidate genes. Future studies of crosstalk among the pathways may provide us a step toward understanding the pathogenic mechanism. This finding indicates the necessity of obtaining family medical history and screening of extended relatives of patients with TAAD for the early identification and treatment of TAAD.